2016
DOI: 10.1016/j.oceaneng.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

An application of fuzzy-AHP to ship operational energy efficiency measures

Abstract: Lowering fuel consumption of ships has gained a great deal of attention in maritime industry with regards to both environmental and economic concerns. The potential for fuel economy in shipping ranging between 25% to 75% is possible by using existing technology and practices and technical improvements in the design of new ship. Despite the existence of many technology and design-based approaches, limitations of emerging these measures has led to discussions about the potential energy savings through operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 71 publications
0
52
0
2
Order By: Relevance
“…The paired comparison criterion in fuzzy AHP methods was performed by applying the fuzzy scale with triangular fuzzy numbers; see Table 8 [93][94][95][96]. For the comparison in pairs of the traditional AHP method, the classic Saaty scale is used, in Table 8 [86].…”
Section: Gis-mcdamentioning
confidence: 99%
“…The paired comparison criterion in fuzzy AHP methods was performed by applying the fuzzy scale with triangular fuzzy numbers; see Table 8 [93][94][95][96]. For the comparison in pairs of the traditional AHP method, the classic Saaty scale is used, in Table 8 [86].…”
Section: Gis-mcdamentioning
confidence: 99%
“…Regarding the application and handling of FMCDA, many studies [43,[79][80][81] have shown that FAHP is a fundamental and widely used method. This method presents a strong ability for tackling the qualitative multi-criteria evaluation problem by combining the concept of fuzzy theory with a hierarchical structure.…”
Section: Extent Analysis Methods On Fuzzy Ahp (Eafahp)mentioning
confidence: 99%
“…The fuzziness of data involved in determining preferences of the various evaluation criteria can be adequately solved through FEAHP. This FEAHP has been comprehensively applied to various fields research [43,44,[83][84][85][86][87]. This paper used FEAHP to solve the Life-City evaluation problem.…”
Section: Extent Analysis Methods On Fuzzy Ahp (Eafahp)mentioning
confidence: 99%
“…It is assumed that AHP method includes high subjectivity. Fuzzy AHP effectively could reduce the human thoughts' unclarity by providing value's interval [13]. There is the weighting comparison's result for AHP and Fuzzy AHP provided by experts in table 3.…”
Section: Stage Of Analyzementioning
confidence: 99%